Synthesis, spectroscopic characterization, molecular docking and in vitro cytotoxicity investigations on 8-Amino-6-Methoxy Quinolinium Picrate: a novel breast cancer drug. Issue 5 (24th March 2023) - Geetha, R.; Meera, M. R.; Vijayakumar, C.; Premkumar, R.; Milton Franklin Benial, A.
Abstract: Density Functional Theory (DFT) studies of the 8-Amino-6-Methoxy Quinolinium Picrate (8A6MQP) molecule have been carried out with extensive and accurate investigations of detailed vibrational and spectroscopic investigations as well as validated experimentally. The 8A6MQP sample was synthesized and characterized using FT-IR, FT-Raman, FT-NMR and UV-Vis spectroscopic techniques. Subsequently, the optimized molecular structure and harmonic resonance frequencies of the molecule were computed based on DFT/B3LYP method with a 6-311G++(d, p) basis set using the Gaussian 09 program. The experimental and calculated vibrational wavenumbers were assigned. The absorption spectrum of the molecule was computed in the liquid phase (ethanol), which exhibits n to л* electronic transition and compared with the observed UV-Vis spectrum. Frontier molecular orbital analysis shows the molecular reactivity and kinetic stability of the molecule. The Mulliken atomic charge distribution and molecular electrostatic potential surface analysis of the molecule validate the reactive site of the molecule. The natural bond orbital analysis proves the bioactivity of the molecule. Molecular docking analysis indicates that the 8A6MQP molecule inhibits the action of DNA topoisomerase 2-alpha protein, which is associated with breast cancer. In addition, the in vitro cytotoxicity analysis of the 8A6MQP molecule against human cervical cancer cell lines (ME180) and human breast cancer cell lines (MDA MB 231) were determined by MTT assay, which evidences that the title molecule exhibits higher inhibition against the breast cancer cell lines compared to that of cervical cancer cell lines. Hence, the present study paves the way for the development of novel drugs in the treatment of breast cancer. Communicated by Ramaswamy H. Sarma